2005
DOI: 10.1021/jm0492498
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacology of N-Substituted Piperazine-2,3-dicarboxylic Acid Derivatives Acting as NMDA Receptor Antagonists

Abstract: The binding site for competitive NMDA receptor antagonists is on the NR2 subunit, of which there are four types (NR2A-D). Typical antagonists such as (R)-AP5 have a subunit selectivity of NR2A > NR2B > NR2C > NR2D. The competitive NMDA receptor antagonist (2R,3S)-(1-biphenylyl-4-carbonyl)piperazine-2,3-dicarboxylic acid (PBPD, 16b) displays an unusual selectivity with improved relative affinity for NR2C and NR2D vs NR2A and NR2B. Analogues of 16b bearing aroyl or aryl substituents attached to the N(1) position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…The role of different NMDAR subtypes in mediating the inhibitory effect of A␤ on high frequency stimulation (HFS) induction of LTP at hippocampal CA1 synapses was assessed in vivo, using antagonists for different GluN2 subunits. We compared the effect of the antagonist NVP-AAM077 with approximately 10-fold selectivity for GluN2A over GluN2B and approximately 2-fold over GluN2C/D, the antagonist ifenprodil which has Ͼ approximately 200-fold selectivity for GluN2B over other GluN2 subunits, and the antagonist UBP141 with Ͼ approximately 5-fold selectivity for GluN2C/D over GluN2A/B (7,24). First we titrated the agents against LTP to find doses that were approximately half the threshold for inhibition of NMDAR-dependent synaptic plasticity (Fig.…”
Section: Abrogation Of A␤-mediated Disruption Of Hippocampal Synapticmentioning
confidence: 99%
“…The role of different NMDAR subtypes in mediating the inhibitory effect of A␤ on high frequency stimulation (HFS) induction of LTP at hippocampal CA1 synapses was assessed in vivo, using antagonists for different GluN2 subunits. We compared the effect of the antagonist NVP-AAM077 with approximately 10-fold selectivity for GluN2A over GluN2B and approximately 2-fold over GluN2C/D, the antagonist ifenprodil which has Ͼ approximately 200-fold selectivity for GluN2B over other GluN2 subunits, and the antagonist UBP141 with Ͼ approximately 5-fold selectivity for GluN2C/D over GluN2A/B (7,24). First we titrated the agents against LTP to find doses that were approximately half the threshold for inhibition of NMDAR-dependent synaptic plasticity (Fig.…”
Section: Abrogation Of A␤-mediated Disruption Of Hippocampal Synapticmentioning
confidence: 99%
“…Subsequent determination of K B from Schild analysis suggested that the selectivity was only ϳ5-fold, precluding its use as a selective tool (Frizelle et al, 2006;Neyton and Paoletti, 2006). Antagonists with bulky, hydrophobic substituents, such as phenanthrene-piperazine dicarboxylic acid analogs (2S,3R)-1-(phenanthren-2-carbonyl)piperazine-2,3-dicarboxylic acid and (2R,3S)-1-(phenanthrenyl-3-carbonyl)piperazine-2,3-dicarboxylic acid (UBP141), show only modest 10-fold higher affinity for GluN2C-and GluN2D-containing receptors over GluN2A andGluN2B (Feng et al, 2004, 2005;Morley et al, 2005;Costa et al, 2009) (Table 11). Subunit selectivity for competitive antagonists may be difficult to achieve because of high homology among GluN2 subunit LBDs.…”
Section: Glun2mentioning
confidence: 99%
“…The compound PPDA is distinct in having a 2-to 5-fold higher affinity for NR2C-or NR2D-containing receptors than that for receptors containing either NR2A or NR2B Morley et al, 2005). Although PPDA has a low degree of selectivity, studies comparing its action to other competitive antagonists have been able to identify differing physiological actions for NMDA receptors containing different NR2 subunits.…”
mentioning
confidence: 99%